Literatur Review : Hubungan Antara Motivasi Berwirausaha dan Keberlanjutan UMKM di Indonesia - larispa, mega; aulia, jesika; nailah rizky, Mutiara; rahmadani siregar, naurah (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2023)
This study aims to examine the relationship between entrepreneurial motivation and the sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia. In the face of challenges such as limited capital, lack of technology access, and economic crises, entrepreneurs' motivation is considered an internal factor that influences business resilience and continuity. This research employs a literature review method by analyzing ten relevant national academic journals. The discussion focuses on how intrinsic motivation (such as independence and personal fulfillment) and extrinsic motivation (such as financial gain and social recognition) drive MSME actors to survive, innovate, and grow. The findings reveal that the majority of the reviewed journals support the idea that motivation has a positive and significant impact on business success and sustainability, both in normal conditions and during crises such as the pandemic. Although one journal reported an insignificant effect, this is attributed to specific contextual factors. The benefit of this study lies in its contribution to policymakers, business actors, and training institutions, emphasizing the importance of integrating motivational development into sustainable MSME empowerment programs.